(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nanofluids have been an area of interest since the past decade due to their number of potential applications in various fields. Their physical properties have been studied on a vast scale like thermal conductivity, viscosity etc. we present in this paper a study on the existing explanations on the mechanism of the anomalous thermal conductivity enhancement and varied experimental results put forward by the scientific community so far. The paper discovers that a much more deep study is needed both on experimental and theoretical platform in order to derive maximum from these emerging smart fluids.